Dampak Tradisi Meupahukh Terhadap Perkawinan Dibawah Umur dalam Masyarakat Suku Alas di Aceh Tenggara - Fadhila, Dina (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
This study aims to analyze the practice of mepahukh tradition in the Alas tribal community as a process of finding a mate for young people and young women of the Alas tribe who have an impact on child marriage. In this study the author uses a type of field research (field research) and is qualitative research. Through the approach of sociology of Islamic law, the author tries to examine the impact of the traditional practice of mepahukh child marriage in the Alas tribal community. As for this study, there are also two types of data sources used by the author, namely primary data and secondary data. The results showed that the practice of Meupahukh tradition in the Alas tribal community, especially in Alur Buluh Village, Bukit Tusam District, Southeast Aceh Regency, had an impact on child marriage. As through social construction theory, Peter Berger and Thomas Luckman see society as a process that takes place in three dialectical moments at once, namely externalization, the impact of Meupahukh tradition on underage marriage occurred because there was no policy from the government, neither local regulations nor policies from the Aceh customary council that regulated the minimum age of marriage. Objectification, assuming that marriage is an easy thing and as a way to get out of the village or area where they live and economic factors. Internalization, there is no age limit for young men and women to follow the procession of the Meupahukh tradition even this tradition is also followed by children who are still in elementary school. The involvement of children in the Meupahukh tradition can certainly encourage underage marriage.